Consumption of the Artificial Sweetener Acesulfame Potassium throughout Pregnancy Induces Glucose Intolerance and Adipose Tissue Dysfunction in Mice. Issue 7 (22nd April 2020) - Plows, Jasmine F; Morton-Jones, Jacob; Bridge-Comer, Pania E; Ponnampalam, Anna; Stanley, Joanna L; Vickers, Mark H; Reynolds, Clare M
ABSTRACT: Background: Sugar-sweetened beverage consumption is associated with metabolic dysfunction. Artificially sweetened beverages (ASBs) are often promoted as an alternative. However, evidence for the safety of ASB consumption during pregnancy is lacking. Objectives: The effects of sugar-sweetened beverage and ASB consumption during pregnancy in mice were examined, and we hypothesized that both sugar-sweetened beverages and ASBs would impair maternal metabolic function. Methods: Pregnant female C57BL/6J mice received control drinking water (CD), high-fructose corn syrup (Fr; 20% kcal intake; 335 mM), or the artificial sweetener acesulfame potassium (AS; 12.5 mM) in their drinking water, from gestational day (GD) 0.5 ( n = 8/group). Body weights and food and water intakes were assessed every second day, an oral-glucose-tolerance test (OGTT) was performed at GD 16.5, and mice were culled at GD 18.5. RT-PCR was carried out on adipose tissue, liver, and gut. Adipose tissue morphology was assessed using histological methods. In a separate cohort of animals, pregnancy length was assessed. Repeated-measures ANOVA was performed for the OGTT and weight gain data. All other data were analyzed by 1-way ANOVA. Results: Fr and AS significantly impaired glucose tolerance, as demonstrated by OGTT (21% and 24% increase in AUC, respectively; P = 0.0006). Fr and AS reduced expression of insulin receptor (39.5% and 33% reduction, respectively; P = 0.02) and peroxisome proliferator–activated receptor γ (45.2% and 47%, respectively; P = 0.039), whereas Fr alone reduced expression of protein kinase B (36.9% reduction; P = 0.048) and resulted in an increase in adipocyte size and leptin concentrations (40% increase; P = 0.03). AS, but not Fr, reduced male fetal weight (16.5% reduction; P = 0.04) and female fetal fasting blood glucose concentration at cull (20% reduction; P = 0.02) compared with CD. AS significantly reduced the length of pregnancy compared with the CD and Fr groups (1.25 d shorter; P = 0.02). Conclusions: Fr and AS consumption were associated with maternal metabolic dysfunction in mice. AS was also associated with reduced fetal growth and fetal hypoglycemia. Therefore, ASBs may not be a beneficial alternative to sugar-sweetened beverages during pregnancy.